Study of the d (d, n)3He reaction in the astrophysical energy region with the use of the Hall accelerator; The European Physical Journal A; Vol. 36, iss. 2 - Bystritsky V. M.; Gerasimov V. V.; Krylov A. R.; Parzhitskii S. S.; Anan'in P. S.; Dudkin G. N. Gennadiy Nikolaevich; Kaminsky V. L. Valery Ludvigovich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Petrov A. V.; Mesyats G. A. Gennady Andreyevich; Filipowicz M.; et al. (2008, 2008)
Title screen